Patologías de daño y evaluación geo-referenciada de pavimento rígido del tramo de la vía Santa Rosa "Y" de Corralitos (44+357 - 59+660) con una longitud de aproximada de 15.3 Km. - Cando Moreira, Katherine Yessenia (2015)
The Santa Rosa - "Y" of Corralitos characterized today as "Highway Rio Seven- Huaquillas" is the Troncal Panamericana de la Costa E25 coming from Huaquillas, Arenillas, Santa Rosa, belonging to the National Road Network and has with rigid pavement structure. In this work a detailed qualification pathway analysis was performed, referencing deterioration of all kinds and severity contributing a database, given by the geo-referenced assessment and pathology damage it. a thorough diagnosis of the pathologies of damage suffered by the rigid pavement in its present state is required. The tour of the track in its entirety, bibliographic research and on the web, accompanied by the experiences of the people involved in this investigation justified the preparation of tables, drawings and written as a review of the examination that was performed at the same sequence and have an inventory with respect to the various pathologies that has as a whole. The results obtained from the evaluation of the section of the Santa Rosa - "Y" Corralitos, such as the degree of deterioration of the road is 1.86%, and according to their severity accounts for 1.178% low severity, 0.522% medium severity and 0.166% to high severity, damage predominating transverse cracks are established according to the methods used. They will be considered for subsequent routing to appropriate and accurate repairs rigid pavement road projects within the province.